Protective effect of Cordyceps sinensis extract on lipopolysaccharide-induced acute lung injury in mice. Issue 6 (25th June 2019) - Fu, Shuiqiao; Lu, Weina; Yu, Wenqiao; Hu, Jun
Abstract : Background: To study the protective effect of Cordyceps sinensis extract (Dong Chong Xia Cao in Chinese [DCXC]) on experimental acute lung injury (ALI) mice. Methods and results: ALI model was induced by intratracheal-instilled lipopolysaccharide (LPS, 2.4 mg/kg) in BALB/c male mice. The mice were administrated DCXC (ig, 10, 30, 60 mg/kg) in 4 and 8 h after receiving LPS. Histopathological section, wet/dry lung weight ratio and myeloperoxidase activity were detected. Bronchoalveolar lavage fluid (BALF) was collected for cell count, the levels of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), interleukin-6 (IL-6) and nitric oxide (NO) in BALF was detected by ELISA, the protein and mRNA expression of nuclear factor-κB p65 (NF-κB p65), inducible NO synthase (iNOS) and cyclooxygenase-2 (COX-2) in lung tissue was detected by Western blot and RT-PCR. The result showed that DCXC could reduce the degree of histopathological injury, wet/dry weight ratio (W/D ratio) and myeloperoxidase activity ( P <0.05) with a dose-dependent manner. The increased number of total cells, neutrophils and macrophages in BALF were significantly inhibited by DCXC treatment ( P <0.05). The increased levels of TNF-α, IL-1β, IL-6 and NO in BALF after LPS administration was significantly reduced by DCXC ( P <0.05). In addition, the increased protein and mRNA levels of iNOS, COX-2 and NF-κB p65 DNA binding ability in LPS group were dose-dependently reduced by DCXC treatment ( P <0.05). Conclusion: DCXC could play an anti-inflammatory and antioxidant effect on LPS-induced ALI through inhibiting NF-κB p65 phosphorylation, and the expression of COX-2 and iNOS in lung. The result showed that DCXC has a potential protective effect on the ALI.